Probing the mind of God: divine beliefs and credences - Jackson, Elizabeth (Religious studies, 2022)
Although much has been written about divine knowledge, and some on divine beliefs, virtually nothing has been written about divine credences. In this article we comparatively assess four views on divine credences: (1) God has only beliefs, not credences; (2) God has both beliefs and credences; (3) God has only credences, not beliefs; and (4) God has neither credences nor beliefs, only knowledge. We weigh the costs and benefits of these four views and draw connections to current discussions in philosophical theology.